Development of Insect-Resistant Hybrid Rice by Introgressing the Bt Gene from Bt Rice Huahui 1 into II-32A/B, a Widely Used Cytogenic Male Sterile System - Yun-song LAI; Hai-qing HUANG; Meng-yun XU; Liang-chao WANG; Xiao-bo ZHANG; Ji-wen ZHANG; Ju-min TU (Journal of Integrative Agriculture, 2014)
Huahui 1 is an elite transgenic male sterile restorer line of wild rice abortive-type that expresses a Bacillus thuringiensis (Bt) δ-endotoxin and provides effective and economic control of lepidopteran insects. To exploit Huahui 1 to develop a new Bt rice, the insertion site of the Bt gene was determined by thermal asymmetric interlaced PCR (TAIL-PCR). Bt was located in the promoter region of LOC.Os10g10360, approximately 5.35 Mb from the telomere of the short arm of chromosome 10. For the first time, a Bt cytoplasmic male sterile (CMS) system was developed by introgressing Bt from Huahui 1. The recipient CMS system used consisted of Indonesia paddy rice-type II-32B (maintainer line) and II-32A (male sterile line). Marker-assisted selection was used to increase selection efficiency in the backcrossing program. In BC5F1, the Bt plant 85015-8 was selected for further analyses, as it had the highest SSR marker homozygosity. In addition, the linkage drag of the foreign Bt gene in 85015-8 was minimized to 8.01-11.46 Mb. The foreign Bt gene was then delivered from 85015-8 into II-32A. The resultant Bt II-32A and Bt II-32B lines were both resistant to lepidopteran in field trials, and agronomic traits were not disturbed. The maintainability of II-32B, and the male sterility and general combining ability of II-32A, were not affected by the Bt introgression. This study demonstrates a simple and fast approach to develop Bt hybrid rice.